Hypertriglyceridemic Waist: A Simple Marker of High‐Risk Atherosclerosis Features Associated With Excess Visceral Adiposity/Ectopic Fat. Issue 8 (13th April 2018) - LeBlanc, Stéphanie; Coulombe, François; Bertrand, Olivier F.; Bibeau, Karine; Pibarot, Philippe; Marette, André; Alméras, Natalie; Lemieux, Isabelle; Després, Jean‐Pierre; Larose, Eric
Abstract : Background: Subclinical atherosclerosis identification remains challenging; abdominal visceral adiposity may improve risk stratification beyond traditional cardiovascular risk factors. Hypertriglyceridemic waist, a visceral adiposity marker combining elevated triglycerides (≥2 mmol/L) and waist circumference (≥90 cm), has been related to carotid atherosclerosis, although associations with high‐risk features, including lipid‐rich necrotic core (LRNC), remain unknown. We tested the hypothesis that hypertriglyceridemic waist is an independent marker of high‐risk atherosclerosis features. Methods and Results: In this cross‐sectional study including 467 white men (mean age, 45.9±14.8 years; range 19.4–77.6 years), carotid atherosclerosis characteristics were examined by magnetic resonance imaging and associations with hypertriglyceridemic waist and benefits beyond Framingham Risk Score (FRS) and Pathobiological Determinants of Atherosclerosis in Youth (PDAY) were determined. Subclinical carotid atherosclerosis was present in 61.9% of participants, whereas 50.1% had LRNC. Hypertriglyceridemic waist was associated with carotid maximum wall thickness ( P =0.014), wall volume ( P =0.025), normalized wall index ( P =0.004), and Carotid Atherosclerosis Score (derived from wall thickness and LRNC; P =0.049). Hypertriglyceridemic waist was associated with carotid LRNC volume beyond FRS ( P =0.037) or PDAY ( P =0.015), contrary to waist circumference alone (both P >0.05). Although 69.7% and 62.0% of participants with carotid atherosclerosis and/or LRNC were not high‐risk by FRS or PDAY, respectively, hypertriglyceridemic waist correctly reclassified 9.7% and 4.5% of them, respectively. Combining hypertriglyceridemic waist with FRS (net reclassification improvement=0.17; P <0.001) or PDAY (net reclassification improvement=0.05; P =0.003) was superior to each score alone in identifying individuals with carotid atherosclerosis and/or LRNC. Conclusions: Hypertriglyceridemic waist is an independent marker of carotid high‐risk atherosclerosis features in men, improving on FRS and PDAY risk score.